1983
DOI: 10.1177/088840648300600402
|View full text |Cite
|
Sign up to set email alerts
|

Teaching LD Adolescents

Abstract: The National Secondary School Survey was conducted to obtain "state-of-the-art" information about service delivery to learning disabled and emotionally disturbed adolescents. Public

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In particular, there is a dearth of information available regarding teacher practices, teaching behaviors, and related student activities within secondary programs. In fact, a search of the published literature yielded only nine studies providing information about secondary resource room programs (Benz & Halpern, 1986;Brozovich & Kotting, 1984;D'Alonzo & Wiseman, 1978 ;Deshler, Lowrey, & Alley, 1979;Gerber & Griffin, 1983;Lerner, Evans, & Minors, 1977;McLeod & Armstrong,1982;McNutt & Heller, 1978;Wells, Schmid, Algozzine, & Maher, 1983). In these studies, researchers examined program characteristics such as teacher and student demographics and caseload size.…”
mentioning
confidence: 95%
“…In particular, there is a dearth of information available regarding teacher practices, teaching behaviors, and related student activities within secondary programs. In fact, a search of the published literature yielded only nine studies providing information about secondary resource room programs (Benz & Halpern, 1986;Brozovich & Kotting, 1984;D'Alonzo & Wiseman, 1978 ;Deshler, Lowrey, & Alley, 1979;Gerber & Griffin, 1983;Lerner, Evans, & Minors, 1977;McLeod & Armstrong,1982;McNutt & Heller, 1978;Wells, Schmid, Algozzine, & Maher, 1983). In these studies, researchers examined program characteristics such as teacher and student demographics and caseload size.…”
mentioning
confidence: 95%
“…Others have suggested the importance of including career, vocational, and applied life skills training in secondary programs for the handicapped (Irvine, Goodman, & Mann, 1978). Nonetheless, in a recent survey of approximately 1,500juniar and senior high school special education teachers, Wells, Schmid, Algozzine, and Maher (1983) found that secondary teachers continue to spend most of their time either remediating basic skills or tutoring students on content-area material. Such a discrepancy between recommended and actual practice raises serious questions with regard to how state and local universities are responding to teachereducation needs in this area.…”
mentioning
confidence: 96%